Parent Activation in the Neonatal Intensive Care Unit - Skeens, Ryan; Cavanaugh, Kerri L.; Cronin, Robert; Chen, QinGxia; Liu, Yuhan; Huth, Hannah; Jackson, Gretchen P. (American Journal of Perinatology, 2021)
Objective Patient activation is the knowledge, skills, and confidence to manage one's health; parent activation is a comparable concept related to a parent's ability to manage a child's health. Activation in adults is a modifiable risk factor and associated with clinical outcomes and health care utilization. We examined activation in parents of hospitalized newborns observing temporal trends and associations with sociodemographic characteristics, neonate characteristics, and outcomes.Study Design Participants included adult parents of neonates admitted to a level-IV neonatal intensive care unit in an academic medical center. Activation was measured with the 10-item Parent version of the Patient Activation Measure (P-PAM) at admission, discharge, and 30 days after discharge. Associations with sociodemographic variables, health literacy, clinical variables, and health care utilization were evaluated.Results A total of 96 adults of 64 neonates were enrolled. The overall mean P-PAM score on admission was 81.8 (standard deviation [SD] = 18), 88.8 (SD = 13) at discharge, and 86.8 (SD = 16) at 30-day follow-up. Using linear mixed regression model, P-PAM score was significantly associated with timing of measurement. Higher P-PAM scores were associated with higher health literacy (p = 0.002) and higher in mothers compared to fathers (p = 0.040). There were no significant associations of admission P-PAM scores with sociodemographic characteristics. Parents of neonates who had a surgical diagnosis had a statistically significant (p = 0.003) lower score than those who did not. There were no associations between discharge P-PAM scores and neonates' lengths of stay or other indicators of illness severity.Conclusion Parental activation in the NICU setting was higher than reported in the adult and limited pediatric literature; scores increased from admission to discharge and 30-day postdischarge. Activation was higher in mothers and parents with higher health literacy. Additional larger scale studies are needed to determine whether parental activation is associated with long-term health care outcomes as seen in adults.Key Points
Keywords: activation; parent activation; P-PAM; neonatal intensive care unit; health care outcomes; health literacy